From redevelopment to urban From redevelopment to urban inclusion of disadvantaged neighborhoods. The example of the Sidi Salem district - Annaba-of disadvantaged neighborhoods. The example of the Sidi Salem district - Annaba- - Laifa, Imen; MEBIROUK, Hayet (Journal of Human Sciences, 2021)
After independence, the city of Annaba launched social housing programs in peri-urban areas in order to meet the high demand for housing generated by the city's industrialization policy and to alleviate its overcrowded center. However, this strategy did not succeed in the function of the habitat, but allowed the birth of dormitory cities where many problems arise. The Sidi Salem district, administratively belonging to the Municipality of El-Bouni, illustrates this policy perfectly. Isolated from the city and even its Commune, the district of Sidi-Salem is a fertile ground for urban requalification and rehabilitation. Often used to offer a new vocation to the territory by betting on its development or redevelopment opportunities, the notion of urban requalification is reinforced by the consolidation of the environment concerned, the design of new spaces and projects in favour of a social and functional mix. As part of this issue, our objective is to know the potential of the district in order to revitalize it through new functions and a new vocation. To do so, we will adopt a participative approach by involving the inhabitants in this revitalization process whose stake is the insertion of the district both in its Commune and in the city by improving the socio-urban, economic and also environmental framework.